An energy balance of front crawl - Zamparo, P.; Pendergast, D. R.; Mollendorf, E. J.; Termin, A.; Minetti, A. E. (European Journal of Applied Physiology, 2005)
With the aim of computing a complete energy balance of front crawl, the energy cost per unit distance (C= E_ v 1, where E_ is the metabolic power and v is the speed) and the overall efficiency (go=Wtot/C, where Wtot is the mechanical work per unit distance) were calculated for subjects swimming with and without fins. In aquatic locomotion Wtot is given by the sum of: (1) Wint, the internal work, which was calculated from video analysis, (2) Wd, the work to overcome hydrodynamic resistance, which was calculated from measures of active drag, and (3) Wk, calculated from measures of Froude efficiency (gF). In turn, gF=Wd/(Wd+Wk) and was calculated by modelling the arm movement as that of a paddle wheel. When swimming at speeds from 1.0 to 1.4 m s 1, gF is about 0.5, power to overcome water resistance (active body drag · v) and power to give water kinetic energy increase from 50 to 100 W, and internal mechanical power from 10 to 30 W. In the same range of speeds E_ increases from 600 to 1,200 W and C from 600 to 800 J m 1. The use of fins decreases total mechanical power and C by the same amount (10-15%) so that go (overall efficiency) is the same when swimming with or without fins [0.20 (0.03)]. The values of go are higher than previously reported for the front crawl, essentially because of the larger values ofWtot calculated in this study. This is so because the contribution of Wint to Wtot was taken into account, and because gF was computed by also taking into account the contribution of the legs to forward propulsion.